LEARNER AUTONOMY IN THE CONTEXT OF MB-KM POLICY: UNIVERSITY TEACHERS’ BELIEFS AND PRACTICES - Fitri Aprianti; Eline Rozaliya Winarto (English Review: Journal of English Education, 2023)
Learner autonomy has been regarded as the point of pivotal in the implementation of the new Curriculum Merdeka. This study aims to describe the lecturers’ beliefs and practices in learner autonomy (LA) within the implementation of MBKM (Merdeka Belajar-Kampus Merdeka) policy. Applying a qualitative method with a case study design, this research involved 56 English Education Program university lecturers whose working within MBKM policy as the participants for the questionnaire. Then, 5 of the participants were further selected as the respondents of the interview and document analysis. The research reveals that the lecturers were knowledgeable about the notion of LA. It was shown as LA was mentioned in the construction of instructional material and design also in the teaching and learning process. Furthermore, the lecturers believed that LA supports the autonomous leaners’ language development during the implementation of MBKM policy. Two aspects, which are political-technical environment and learning ecosystem, dominated the lecturers’ perspectives in considering that MBKM policy seems to be able to give more educational choices for the learner to study both in and out of the classroom environment. However, it is depicted that, the psychological and sociocultural aspects, such as that of the relatively low degree of the students’ confidence, readiness, and agility in learning, seemed to remain problematic as they tend to hinder the development of LA. Therefore, the lecturers indicated that taking a role in facilitating the students’ LA development is still required to anticipate the obstacles.